Platelet-rich-Plasma in Kombination mit autologer Spongiosa: Eine Alternative bei therapierefraktären Pseudarthrosen? - Hakimi, M.; Jungbluth, Pascal; Thelen, S.; Linhart, W.; Flohe, Sascha; Windolf, J.; Wild, M.; Betsch, Marcel (Unfallchirurg, 2011)
Background: In addition to a stabile osteosynthesis autologous cancellous bone graft remains an essential therapy option in persistent non-union. Despite this therapy regimen persistent non-union can occasionally occur. The aim of this study was to evaluate the treatment of persistent non-union with a combination of platelet-rich plasma (PRP) and autologous cancellous bone. Material and methods: In this prospective study 17 patients with persistent non-union of long bones were treated by a combination of PRP and autologous iliac crest bone. Inclusion criteria were a minimum of one previously failed cancellous bone transplantation and an atrophic non-union persisting for 6-14 months (mean 9 months). The patients were examined clinically and radiologically at intervals of 3, 6 and 9 months postoperatively. Results: After an average time of 17 months (range 15-23 months) the patients were treated by a combination of PRP and autologous cancellous bone. In all cases the non-union was successfully treated and osseous bridging was found radiologically after an average of 5 months (range 4-7 months) without any complications. Conclusion: The combination of PRP and autologous cancellous bone appears to be a safe and effective method for treatment of persistent non-union. The use of PRP does not result in substantial additional costs. Allergies and graft versus host reactions are not expected because of the autologous origin. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Autologous cancellous bone; Growth factors; Long bones; Non-union; Platelet-rich plasma